Appunti sui brevia di XI e XII secolo - Ansani, Michele (Scrineum, 2013)
Among the early middle ages documentary heritage, really poor is the quantity of brevia we can examine; but it doesn't mean this kind of record was unusual, as is shown by some formulae of Chartularium langobardicum (10th century). Nevertheless, they begun to frequently appear since mid 11th Century, in order to resolve new claims that changes in politics and social relations brought out (feudal relations as well as, later, legal activity of cities government, and overall extra-judicial settlement of disputes). This survey has the purpose to analyze summarily the phase, between XIth and XIIth Century, in wich recording per breve became a normal option in these circumstances, when a clean pattern was developed by notarial culture - also provided of courts experience - giving breve a form that remind, in some respects, the previous pleas writing schemes.